Infrared Thermography for the Ante Mortem Detection of Bruising in Horses Following Transport to a Slaughter Plant - Roy, Rayappan Cyril; Riley, Christopher B.; Stryhn, Henrik; Dohoo, Ian; Cockram, Michael S. (Frontiers in Veterinary Science, 2019)
Undetected injury of horses sustained during road transport to slaughter is a welfare concern. This study evaluated digital infrared thermography (DT) for the detection of ante-mortem bruising in horses following transport to a slaughter plant. The sensitivity and specificity of the DT camera for the detection of bruises following transport to a slaughter plant was evaluated. DT images were obtained from 93 horses (2-3 horses per load; 40 loads) at a Canadian federally approved slaughter plant. From an elevated platform 5m from the horses, left and right lateral DT images, and one caudal pelvic area image were obtained from each horse. After slaughter the carcasses were examined for bruising (a visually discolored area on the carcass caused by damage to the blood vessels) and findings documented. Sensitivity, specificity, and predictive values were calculated for DT assessment of bruising. The DT approach to bruise detection at the region of interest level of 93 horses (n=186 sides) resulted in a sensitivity of 42% and specificity of 79%. As the sensitivity was low, a more sensitive DT camera and allowing for a longer equilibration time for horses after transport may improve this approach to post transport assessment of subclinical injury.